Penerapan Model Pembelajaran Numbered Heads Together dalam Upaya Meningkatkan Aktivitas Belajar Siswa pada Materi Gelombang pada Kelas XI-A1 SMAN 2 Pamekasan - Sofweturrohmah; Fatihatur Rizqi; Suprianto; Lukluk Ibana; Khalifatur Rahman; Hairuni Indrasari (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to enhance students’ learning activities through the implementation of the Numbered Heads Together (NHT) cooperative learning model in physics classes. This study is a classroom action research conducted in two cycles, each consisting of the planning, implementation, observation, and reflection stages. The implementation of the NHT model involves four main steps: numbering, posing questions, group discussion, and presenting answers. The research subjects were students in Class XI A1 at SMAN 2 Pamekasan. Data were collected using an observation sheet for student learning activities, which included indicators of verbal activity, listening activity, writing activity, mental activity, and emotional activity. The data were analyzed using quantitative descriptive methods by calculating the percentage of student learning activities in each cycle. The results of the study indicate that the implementation of the NHT cooperative learning model was able to enhance students’ learning activities. The average learning activity score increased from 39 in Cycle I which fell into the “fair” category to 53 in Cycle II, which fell into the “good” category. Improvements were also observed across all learning activity indicators, particularly in oral and mental activities, indicating that student engagement improved throughout the learning process. Thus, the Numbered Heads Together (NHT) cooperative learning model is effective in enhancing student learning activities in physics instruction.